Tricuspid regurgitation and atrial fibrillation at baseline independently predict two-year survival after transcatheter aortic valve implantation (TAVI). (3rd October 2022) - Baez, L; Moebius-Winkler, S; Diab, M; Ibrahim, K; Kraeplin, T; Schulze, P C; Franz, M
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is the accepted state-of-the-art treatment for elderly patients suffering from severe symptomatic aortic stenosis (AS). Co-morbidities at baseline are of great impact not only for individual peri-procedural risk stratification but also for the determination of long-term prognosis. The latter is of certain clinical interest, since a variety of co-existing disorders can be effectively treated in addition to TAVI. Purpose: The current study aimed to elucidate the prognostic value of a wide range of baseline characteristics and co-morbidities with respect to long-term survival of TAVI patients in a prospective real-world single-center registry study. Methods: A total of 445 patients with severe AS, which were treated by transfemoral TAVI, were included. A wide range of clinical, laboratory, functional and imaging parameters were prospectively assessed at baseline prior to TAVI. Mortality was recorded at 30 days, 1 year and 2 years after TAVI. Results: The mean age of patients in this typical TAVI cohort was 78.7±7.3 years, 52% were female and the mean STS score was 5±3.9%. The mortality rates were as follows: 3.6% after 30 days, 16.4% after 1 and 22.6% after 2 years. Multivariate analysis could identify the following independent predictors of 2-year mortality assessed at baseline: sex, age, AS entity other than high-gradient, atrial fibrillation (Afib), renal function, relevant TR, systolic pulmonary artery pressure (PAPsys) and six-minute walk distance (SMWD). Among those, the strongest predictive value could be shown for Afib (OR 2.505, CI 1.509–4.157, p<0.001) and TR (OR 2.179, CI 1.105–4.299, p=0.025). Kaplan-Meier survival analysis displayed significantly worse 2-year survival rates in patients suffering from relevant TR (31.6% versus 17.4%, p<0.001) and Afib (29.4% versus 14.8%, p<0.001). Conclusions: Taken together, the results of the current study demonstrate the prognostic value of cardiovascular co-morbidities assessed prior to TAVI. We identified relevant TR and Afib as the strongest independent predictors of long-term mortality in our cohort. Since both conditions are effectively treatable, special emphasis should be placed on the question, which patient might benefit from treatment, e.g., by transcatheter edge-to-edge repair of TR or rhythm control, in addition to TAVI. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Else Kröner-Fresenius-Stiftung, Research Program "Else Kröner-Forschungskolleg AntiAge"